Study of papain-cystatin interaction by intensity fading MALDI-TOF-MS - Shabab, M.; Kulkarni, Mahesh J.; Khan, Mohammad Islam (Protein Journal, 2008)
Intensity fading (IF) matrix assisted laser desorption ionization (MALDI) time of flight (TOF) mass spectrometry (MS ) has become an alternative screening approach for the affinity-binding analysis of proteins and peptides with molecular ligands. In this investigation an attempt has been made to study the protein ligand interaction by intensity fading (IF) MALDI-MS using papain and cystatin as model system for protein-ligand interactions. The intensity fading of cystatin was monitored using various concentration of cystatin ranging from (1 to 8.6 mu M) in presence of target protein, papain. The results indeed indicate that the intensity of cystatin decreases upon addition of papain. Furthermore, for the first time we have used IF-MALDI-MS for determining the number of binding sites for cystatin on papain by Scatchard analysis.
Keywords: intensity fading; MALDI; papain-cystatin; protein-ligand interaction; Scatchard plot

Stress inducible proteinase inhibitor diversity in capsicum annuum - Mishra, Manasi; Mahajan, Neha S.; Tamhane, Vaijayanti A.; Kulkarni, Mahesh J.; Baldwin, Ian T.; Gupta, Vidya S.; Giri, Ashok P. (BMC Plant Biology, 2012)
Background: Wound-inducible Pin-II Proteinase inhibitors (PIs) are one of the important plant serine PIs which have been studied extensively for their structural and functional diversity and relevance in plant defense against insect pests. To explore the functional specialization of an array of Capsicum annuum (L.) proteinase inhibitor (CanPIs) genes, we studied their expression, processing and tissue-specific distribution under steady-state and induced conditions. Inductions were performed by subjecting C. annuum leaves to various treatments, namely aphid infestation or mechanical wounding followed by treatment with either oral secretion (OS) of Helicoverpa armigera or water. Results: The elicitation treatments regulated the accumulation of CanPIs corresponding to 4-, 3-, and 2-inhibitory repeat domains (IRDs). Fourty seven different CanPI genes composed of 28 unique IRDs were identified in total along with those reported earlier. The CanPI gene pool either from uninduced or induced leaves was dominated by 3-IRD PIs and trypsin inhibitory domains. Also a major contribution by 4-IRD CanPI genes possessing trypsin and chymotrypsin inhibitor domains was specifically revealed in wounded leaves treated with OS. Wounding displayed the highest number of unique CanPIs while wounding with OS treatment resulted in the high accumulation of specifically CanPI-4, -7 and -10. Characterization of the PI protein activity through two dimensional gel electrophoresis revealed tissue and induction specific patterns. Consistent with transcript abundance, wound plus OS or water treated C. annuum leaves exhibited significantly higher PI activity and isoform diversity contributed by 3- and 4-IRD CanPIs. CanPI accumulation and activity was weakly elicited by aphid infestation yet resulted in the higher expression of CanPI-26, -41 and -43. Conclusions: Plants can differentially perceive various kinds of insect attacks and respond appropriately through activating plant defenses including regulation of PIs at transcriptional and post-translational levels. Based on the differentially elicited CanPI accumulation patterns, it is intriguing to speculate that generating sequence diversity in the form of multi-IRD PIs is a part of elaborative plant defense strategy to obtain a diverse pool of functional units to confine insect attack.
Keywords: CanPI; Herbivory; Oral secretions; Pin-II type proteinase inhibitors; Plant-insect interaction

Synergistic action of flavin containing NADH dependant azoreductase and cytochrome P450 monooxygenase in azoaromatic mineralization - Oturkar, Chetan C.; Othman, Munif A.; Kulkarni, Mahesh J.; Madamwar, Datta; Gawai, Kachru R. (RSC Advances, 2013)
An alkaliphilic strain Bacillus lentus Bl377 was isolated from contaminated soil of the textile area of Solapur, India. The strain was able to degrade almost 98% of recalcitrant azoic compounds by a mutually regulated process of azoreductase and a monooxygenase system. An enzyme activity study and a periodical carbon monoxide (CO) binding spectra study on a UV-visible spectrophotometer revealed that the intermediate amines formed by typical azoreduction (N=N cleavage), subsequently underwent hydroxylation by the cytochrome P450 monooxygenase (CYP450) system. Azoreductase was purified by chromatographic techniques and characterization by MALDI-TOF substantiated its identity as FMN containing NADH dependent azoreductase of 32 kDa in size. Surprisingly, purified azoreductase showed the highest activity at 80 degrees C and pH 8.0. An increase in the activity of superoxide dismutase after decolorization confirmed the signature of oxidative stress and its involvement in the dismutation of reactive metabolites. Intermediate metabolite analysis by HPLC, GC-MS and FTIR and the removal of total organic carbon (TOC) suggested the azoaromatics' degradation leads to mineralization via a TCA cycle.

Serum responsive proteome reveals correlation between oxidative phosphorylation and morphogenesis in Candida albicans ATCC10231 - Ahmed, Radfan; Kodgire, Santosh; Santhakumari, B.; Patil, Rajendra; Kulkarni, Mahesh J.; Zore, Gajanan (Journal of Proteomics, 2018)
To understand the impact of fetal bovine serum (FBS) on metabolism and cellular architecture in addition to morphogenesis, we have identified FBS responsive proteome of Candida albicans. FBS induced 34% hyphae and 60% pseudohyphae in C. albicans at 30 C while 98% hyphae at 37 C. LC-MS/MS analysis revealed that 285 proteins modulated significantly in response to FBS at 30 degrees C and 37 degrees C. Out of which 152 were upregulated and 62 were downregulated at 30 degrees C while 18 were up and 53 were downregulated at 37 degrees C. Functional annotation suggests that FBS may inhibit glycolysis and fermentative pathway and enhance oxidative phosphorylation (OxPhos), TCA cycle, amino acid and fatty acid metabolism indicating a use of alternative energy source by C. albicans. OxPhos inhibition assay using sodium azide corroborated the correlation between inhibition of glycolysis and enhanced OxPhos with pseudohyphae formation. C. albicans induced hyphae in response to FBS irrespective of down regulation of Rasl,Asrl/Asr2, indicates the possible involvement of MAPK and cAMP-PKA independent pathway. The Cell wall of cells grown in presence of FBS at 30 degrees C was rich in mannan, Beta 1,3glucan and chitin while membranes were rich in ergosterol compared to those grown at 37 degrees C. Significance of the study: This is the first study suggesting a correlation between OxPhos and morphogenesis especially pseudohyphae formation in C. albicans. Our data also indicate that fetal bovine serum (FBS) induced morphogenesis is multifactorial and may involve MAPK and cAMP-PKA independent pathway. In addition to morphogenesis, our study provides an insight in to the modulation of metabolism and cellular architecture of C. albicans in response to FBS.
Keywords: analysis; Candida albicans; Fetal bovin serum; Liquid chromatography mass spectrometry; morphogenesis; Oxidative phosphorylation; pathogenicity

SWATH-MS based quantitative proteomics analysis to evaluate the antileishmanial effect of Commiphora wightii- Guggul and Amphotericin B on a clinical isolate of Leishmania donovani - Bar Routaray, Chinmayee; Bhor, Renuka; Bai, Shakuntala; Kadam, Nitin Suryakant; Jagtap, Surabhi; Doshi, Pooja Jignesh; Sundar, Shyam; Sawant, Sangeeta; Kulkarni, Mahesh J.; Pai, Kalpana (Journal of Proteomics, 2020)
The present study provides comprehensive proteomics analyses of the response of L. donovani parasite to pharamacological stress in vitro. Identification of differentially expressed proteins with associated molecular functions and metabolic pathways, clearly provides an insight into the potential mechanism of the antileishmanial effects as well as a comparative response of the parasite to Guggul and AmB. Treatment of parasite with AmB results in an enhanced modulatory mechanism to counteract the drug induced stress which may have contributed to relapse. In the case of Guggul treatment, an effective antipromastigote activity was observed, which is being reported for the first time. Thus, a deeper understanding of the molecular pathways in the Leishmania parasite in response to pharmacological stress would help in designing novel and effective strategies in targeting the key molecules essential for parasite survival. It will also help in screening of new lead molecules targeting these vital pathways which could be used as an adjunct therapy along with the limited repertoire of antileishmanial drugs.

SWATH-MS based quantitative proteomics analysis to evaluate the antileishmanial effect of Commiphora wightii- Guggul and amphotericin B on a clinical isolate of Leishmania donovani (vol 223, 103800, 2020) - Routaray, Chinmayee Bar; Bhor, Renuka; Bai, Shakuntala; Kadam, Nitin Suryakant; Jagtap, Surabhi; Doshi, Pooja Jignesh; Sundar, Shyam; Sawant, Sangeeta; Kulkarni, Mahesh J.; Pai, Kalpana (Journal of Proteomics, 2021)
Drug resistance and relapse after treatment of visceral leishmaniasis (VL) with the chemotherapeutic drugs has impeded the VL elimination programme especially, in the endemic region of Bihar, India. Currently, Antimonials (Sbv) have been rendered obsolete (Bihar) as frequent treatment failure and relapse in Sbv treated patient's warrants greater vigilance and attention to the limited drugs. A clinical isolate of L.donovani obtained from an Amphotericin B (AmB) relapse patient was evaluated for its susceptibility to AmB and a hyperlipidemic drug Guggul. The evaluation of susceptibility or resistance to any drug still relies on in vitro assay on promastigote and amastigote stages of Leishmania spp. as there are no validated markers which can ascertain drug resistance in Leishmania. The anti-promastigote effect of AmB and Guggul were demonstrated by significant cellular and morphological changes exhibiting apoptosis-mediated cell death. To further illustrate the molecular mechanism of the parasite's response upon exposure to either AmB and Guggul, sequential window acquisition of all theoretical fragment ion spectra mass spectrometry (SWATH-MS) for quantitative proteomics analysis was performed along with computational data analysis; revealing considerable differences in the proteome profiles which could be regarded as putative markers for resistance or drug targets for development of therapeutic antileishmanials.

Stacking herbicide detoxification and resistant genes improves glyphosate tolerance and reduces phytotoxicity in tobacco (Nicotiana tabacum L.) and rice (Oryza sativa L.) - Vennapusa, Amaranatha Reddy; Agarwal, Subham; Hm, Hanumanth Rao; Aarthy, Thiagarayaselvam; Babitha, K. C.; Thulasiram, V. Hirekodathakallu; Kulkarni, Mahesh J.; Melmaiee, Kalpalatha; Sudhakar, Chinta; Udayakumar, M.; Vemanna, Ramu S. (Plant Physiology and Biochemistry, 2022)
Glyphosate residues retained in the growing meristematic tissues or in grains of glyphosate-resistant crops affect the plants physiological functions and crop yield. Removing glyphosate residues in the plants is desirable with no penalty on crop yield and quality. We report a new combination of scientific strategy to detoxify glyphosate that reduces the residual levels and improve crop resistance. The glyphosate detoxifying enzymes Aldo-keto reductase (AKR1) and mutated glycine oxidase (mGO) with different modes of action were co-expressed with modified EPSPS, which is insensitive to glyphosate in tobacco (Nicotiana tabacum L.) and rice (Oryza sativa L.). The transgenic tobacco plants expressing individual PsAKR1, mGO, CP4-EPSPS, combinations of PsAKR1:CP4EPSPS, PsAKR1:mGO, and multigene with PsAKR1: mGO: CP4EPSPS genes were developed. The bio-efficacy studies of in-vitro leaf regeneration on different concentrations of glyphosate, seedling bioassay, and spray on transgenic tobacco plants demonstrate that glyphosate detoxification with enhanced resistance. Comparative analysis of the transgenic tobacco plants reveals that double and multigene expressing transgenics had reduced accumulation of shikimic acid, glyphosate, and its primary residue AMPA, and increased levels of sarcosine were observed in all PsAKR1 expressing transgenics. The multigene expressing rice transgenics showed improved glyphosate resis-tance with yield maintenance. In summary, results suggest that stacking genes with two different detoxification mechanisms and insensitive EPSPS is a potential approach for developing glyphosate-resistant plants with less residual content.
Keywords: Detoxification; Gene stacking; Glyphosate; Herbicide; Multigene; Residual toxicity; Resistant; rice; Tobacco; Transgenics

Supramolecular polyplexes from Janus peptide nucleic acids (bm-PNA-G5): self-assembled bm-PNA G-quadruplex and its tetraduplex with DNA - Todkari, Iranna Annappa; Chaudhary, Preeti; Kulkarni, Mahesh J.; Ganesh, Krishna N. (ORGANIC & BIOMOLECULAR CHEMISTRY, 2024)
Keywords: DOUBLE-HEADED NUCLEOTIDES; ENERGY-TRANSFER; Guanine; MAJOR GROOVE

SWATH-MS reveals that bisphenol A and its analogs regulate pathways leading to disruption in insulin signaling and fatty acid metabolism - Kulsange, Shabda E.; Sharma, Monika; Sonawane, Babasaheb; Jaiswal, Meera R.; Kulkarni, Mahesh J.; Santhakumari, B. (Food and Chemical Toxicology, 2024)
Bisphenol A (BPA) is an endocrine-disrupting chemical (EDC), associated with obesity and insulin resistance. The FDA prohibited the use of BPA-based polycarbonate resins in infant formula packaging; thus, its analogs, viz. Bisphenol S (BPS) and Bisphenol F (BPF) were considered alternatives in epoxy resins, plastics, and food cans. As these analogs might evoke a similar response, we investigated the role of Bisphenols (BPA, BPF, and BPS), on insulin signaling in CHO-HIRc-myc-GLUT4eGFP cells at environmentally relevant concentrations of 2 nM and 200 nM. Insulin signaling demonstrated that Bisphenols reduced phosphorylation of IR and AKT2, GLUT4 translocation, and glucose uptake. This was accompanied by increased oxidative stress. Furthermore, SWATHMS-based proteomics of 3T3-L1 cells demonstrated that Bisphenol-treated cells regulate proteins in insulin resistance, adipogenesis, and fatty acid metabolism pathways differently. All three Bisphenols induced differentially expressed proteins enriched similar pathways, although their abundance differed for each Bisphenol. This might be due to their varying toxicity level, structural differences, and estrogen-mimetic activity. This study has important implications in addressing health concerns related to EDCs. Given that the analogs of BPA are considered alternatives to BPA, the findings of this study suggest they are equally potent in altering fatty acid metabolism and inducing insulin resistance.
Keywords: Bisphenols; Estrogen; Lipid droplet; Mitochondrial beta-oxidation; Oxidative stress; PPAR gamma

Simple freeze-thaw based method for efficient purification of recombinant human proinsulin from inclusion bodies - Rajesh, S.; Jathar, Swaraj; Banarjee, Reema; Sharma, Monika; Palkar, Shivani; Shankar, S. Shiva; Kulkarni, Mahesh J. (Protein Expression and Purification, 2025)
Insulin is a pivotal peptide hormone essential for regulating glucose homeostasis. It has been known for over 100 years, but its production and purification methods are still under improvement. Escherichia coli based bacterial expression system is primarily used for insulin production. The human insulin protein expressed in bacteria usually forms inclusion bodies, complicating the purification process. Traditionally, insulin purification is a timeconsuming process involving urea-based denaturation methods, and various refolding techniques, followed by extensive chromatographic methods. Here, we report an easy and efficient purification of human proinsulin involving freeze-thaw based solubilization method. The extracted proinsulin inclusion bodies are treated with different concentrations of urea, followed by a freeze-thaw based solubilization. The freezing was carried out at various temperatures, mainly -80 degrees C, -20 degrees C, and -196 degrees C to determine the optimum condition for solubilization. Highest solubilization of proinsulin from the inclusion body was achieved with 0.5M urea and -20 degrees C. Further Nickel NTA-based purification was performed, and the purified protein was characterized for disulfide mapping by high-resolution mass spectrometer (HRMS). We also performed glucose uptake assays to validate the functional properties of purified proinsulin. This freeze-thaw based mild solubilization approach is a fast and effective method for getting bioactive proinsulin, which will help further design better purification and processing strategies for insulin production.
Keywords: Diabetes; Disulfide mapping; glucose; insulin; Mass spectrometry